Principles of Practice in Multi-Agent Systems 12th International Conference, PRIMA 2009, Nagoya, Japan, December 14-16, 2009. Proceedings - Yang, Jung-Jin.; Yokoo, Makoto; Ito, Takayuki; Jin, Zhi.; Scerri, Paul.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Agents are software processes that perceive and act in an environment, processing their perceptions to make intelligent decisions about actions to achieve their goals. Multi-agent systems have multiple agents that work in the same environment to achieve either joint or conflicting goals. Agent computing and technology is an exciting, emerging paradigm expected to play a key role in many society-changing practices from disaster response to manufacturing to agriculture. Agent and mul- agent researchers are focused on building working systems that bring together a broad range of technical areas from market theory to software engineering to user interfaces. Agent systems are expected to operate in real-world environments, with all the challenges complex environments present. After 11 successful PRIMA workshops/conferences (Pacific-Rim International Conference/Workshop on Multi-Agents), PRIMA became a new conference titled (3z(BInternational Conference on Principles of Practice in Multi-Agent Systems(3y (Bin 2009. With over 100 submissions, an acceptance rate for full papers of 25% and 50% for posters, a demonstration session, an industry track, a RoboCup competition and workshops and tutorials, PRIMA has become an important venue for multi-agent research. Papers submitted are from all parts of the world, though with a higher representation of Pacific Rim countries than other major multi-agent research forums. This volume presents 34 high-quality and exciting technical papers on multimedia research and an additional 18 poster papers that give brief views on exciting research.s
Technical Papers -- A Market-Based Multi-Issue Negotiation Model Considering Multiple Preferences in Dynamic E-Marketplaces -- Designing Protocols for Collaborative Translation -- An Affective Agent Playing Tic-Tac-Toe as Part of a Healing Environment -- A Multi-agent Model for Emotion Contagion Spirals Integrated within a Supporting Ambient Agent Model -- Statistical Utterance Selection Using Word Co-occurrence for a Dialogue Agent -- On the Impact of Witness-Based Collusion in Agent Societies -- Efficient Methods for Multi-agent Multi-issue Negotiation: Allocating Resources -- Token Based Resource Sharing in Heterogeneous Multi-agent Teams -- Gaia Agents Implementation through Models Transformation -- ONTOMO: Development of Ontology Building Service -- Syncretic Argumentation by Means of Lattice Homomorphism -- Adaptive Adjustment of Starting Price for Agents in Continuous Double Auctions -- SIM-MADARP: An Agent-Based Tool for Dial-a-Ride Simulation -- An Empirical Study of Agent Programs -- A Multiagent Model for Provider-Centered Trust in Composite Web Services -- Memory Complexity of Automated Trust Negotiation Strategies -- Layered Distributed Constraint Optimization Problem for Resource Allocation Problem in Distributed Sensor Networks -- NegoExplorer: A Region-Based Recursive Approach to Bilateral Multi-attribute Negotiation -- Applying User Feedback and Query Learning Methods to Multiple Communities -- An Adaptive Human-Aware Software Agent Supporting Attention-Demanding Tasks -- Designing a Two-Sided Matching Protocol under Asymmetric Information -- Emotion Detection from Body Motion of Human Form Robot Based on Laban Movement Analysis -- HoneySpam 2.0: Profiling Web Spambot Behaviour -- Multimedia Papers -- A Modeling Tool for Service-Oriented Open Multiagent Systems -- Analysis, Comparison and Selection of MAS Software Engineering Processes and Tools -- A Synchronous Model of Mental Rhythm Using Paralanguage for Communication Robots -- Generating Association-Based Motion through Human-Robot Interaction -- SmartContractor: A Distributed Task Assignment System Based on the Simple Contract Net Protocol -- Participatory Simulation Environment gumonji/Q: A Network Game Empowered by Agents -- Industrial Papers -- A Multi-Agent System Based Approach to Intelligent Process Automation Systems -- Non-equity Joints among Small and Medium Enterprises and Innovation Management: An Empirical Analysis Based on Simulation -- Wide-Area Traffic Simulation Based on Driving Behavior Model -- An Agent-Based Framework for Healthcare Support System -- Interpolation System of Traffic Condition by Estimation/Learning Agents -- Poster Papers -- A Fuzzy Rule-Based System for Ontology Mapping -- Where Are All the Agents? On the Gap between Theory and Practice of Agent-Based Referral Networks -- SADE: A Development Environment for Adaptive Multi-Agent Systems -- Recursive Adaptation of Stepsize Parameter for Non-stationary Environments -- Mechanism Design Simulation for Healthcare Reform in China -- Case Learning in CBR-Based Agent Systems for Ship Collision Avoidance -- An Adaptive Agent Model for Emotion Reading by Mirroring Body States and Hebbian Learning -- Agent Evacuation Simulation Using a Hybrid Network and Free Space Models -- Designing Agent Behaviour in Agent-Based Simulation through Participatory Method -- Influence of Social Networks on Recovering Large Scale Distributed Systems -- Dynamic Evolution of Role Taxonomies through Multidimensional Clustering in Multiagent Organizations -- Adaptation and Validation of an Agent Model of Functional State and Performance for Individuals -- A Cooperation Trading Method with Hybrid Traders -- GPGCloud: Model Sharing and Execution Environment Service for Simulation of International Politics and Economics -- Creating and Using Reputation-Based Agreements in Organisational Environments -- Directory Service in the Language Grid for System Integration -- SBDO: A New Robust Approach to Dynamic Distributed Constraint Optimisation -- Evacuation Planning Assist System with Network Model-Based Pedestrian Simulator.
Keywords: Computer science; Computer organization; Software engineering; User interfaces (Computer systems).; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Software Engineering/Programming and Operating Systems; Computer Systems Organization and Communication Networks; Simulation and Modeling; Software Engineering; Electronic books